(untitled) (Economic and Political Thought, 2017)
The article presents comprehensive and detailed deliberations of the issue of formal requirements for members of supervisory boards of companies coowned by the State Treasury. The research method used is a case study of Polska Grupa Zbrojeniowa S.A. (diagnosis of chosen processes taking place in the company PGZ S.A.), supplemented with a detailed analysis of legal regulations in force, a review of literature and court decisions, as well as a discussion of documents including earlier opinions presented by public authorities in their answers to MPs’ queries concerning problems strictly related to previous methods of selecting candidates to senior management posts in companies owned by the State Treasury. The first part of the article presents issues of organizational-legal aspects in the context of methods of selection and formal criteria for members of the supervisory board of PGZ S.A. With reference to the discussed topic, answers to important questions related to several chosen important narrow research issues are given. Particular attention has been drawn to identification and objective discussion of the importance of relevant legal premises, which predetermine differentiated formal requirements for members of supervisory boards in companies co-owned by the State Treasury. Additionally, the author comments on the latest amendments to the regulations in force concerning bans and limitations on the accumulation of positions by members of supervisory boards of companies co-owned by the State Treasury from the perspective of corporate governance mechanisms in PGZ capital group.